Refonder l’entreprise ? Éléments de réflexion pour une autre gestion - Jean-Luc Metzger; Salvatore Maugeri; Daniel Bachet (La Nouvelle Revue du Travail)
The accounting indicators that have been so dominant until now in structuring corporate management are being reduced to simple methods for calibrating financial performance. A large corpus has arisen emphasizing the highly dysfunctional effects of this vision of management, both in terms of “economic efficiency” and employee health. Given such practices, which tend to be hegemonic in nature, the article points out that there are other ways of managing accounts and listed or unlisted companies. Specifically, this involves research focused on something asides from equity holders’ financial interests alone. Proving the relevance of this “other other way of managing”, the article starts by examining the labour and employment effects that are increasingly resulting from the strategies being pursued by industrial and financial groups operating in a deregulated economic environment. It then presents findings from surveys of several SMEs that chose management criteria grounded in the search for “value added” and not in profit maximisation. By nurturing an “enterprise” – and distinguishing this productive entity from the financial “company” that supposedly serves as its host - this other kind of accounting no longer seeks to achieve a financial optimum but tries instead to develop a comprehensive economic and social optimum, one where work and employment are given their true value. The article accepts that certain limitations are inherent to this kind of alternative management – but it does demonstrate that another accounting is possible and can in fact be implemented in those companies who are seeking place their activities on a more sustainable footing. Lastly, it also notes that any attempt at quantification conveys a particular worldview, as well as a certain vision of companies and work. Hence the conclusion that any thinking about changing the rules of the game in economics or business management assumes a profound transformation in accounting practices and theories.